Career capital development in global work: The roles of job scope, career adaptability, and gender dynamics - Mello, Rodrigo; Suutari, Vesa; Kemppinen, Samu (Elsevier, 2025)
Global work, characterized as high-density work, presents unique developmental challenges and opportunities flowing from adapting to diverse job characteristics and roles abroad. This study examines how job scope and career adaptability influence perceived career capital development (PCCD) among expatriates, a key form of global work, drawing on the job characteristics model and career construction theory. Using survey data from 327 expatriates, we test the direct effects of job scope and career adaptability on PCCD and investigate the moderating role of gender in the job scope–PCCD relationship, informed by the frog-pond model and its foundation in social comparison theory. Findings reveal that both job scope and career adaptability positively impact PCCD, supporting their critical role in expatriate career development. Additionally, gender moderates the job scope–PCCD relationship, with women experiencing a stronger effect of job scope on the development of career capital dimensions compared to men. These results highlight the importance of gender dynamics in global careers while reinforcing the broader role of job scope and career adaptability in career capital accumulation. This study contributes to expatriation research by demonstrating that career capital development is multifaceted, shaped not only by individual career adaptability and job scope but also by gender. The findings offer practical insights for organizations seeking to enhance expatriate career development strategies and promote gender equity in global work environments.
Keywords: Global work; Expatriation; Career capital development; Job scope; Career adaptability; Gender; fi=Henkilöstöjohtaminen|en=Human Resource Management|